Volatility Dynamics with Volume and Open Interest : An Empirical Study in the Indian Commodity Market - Gupta, Shashi; Choudhary, Himanshu; Agarwal, D. R. (Indian Journal of Research in Capital Markets, 2015)
This paper examined the relationship between price volatility, volume, and open interest in eight Indian commodity futures; two commodities belong to the agriculture sector, and the remaining six belong to the non agriculture sector. To study the price volatility and its stylized facts like persistence, leverage, clustering in commodity futures, GARCH(1,1) model with adequate autoregressive terms was used. The focus of this study was to examine the volatility persistence in commodity futures return volatility considering the asymmetric effect. ARMA(1,1)–EGARCH(1,1) model augmented by exogenous variables contemporaneous(current) and lagged volume and open interest either separately or jointly was used for estimation. This paper found evidence of leverage effect for castor seed and crude oil. The results of the paper indicated that current volume reduced the volatility persistence more than lagged volume. However, the GARCH effect did not vanish completely. However, the volume and open interest were ineffective in explaining the GARCH effect for energy commodities, which implies the inefficiency of the EGARCH model, which is later confirmed by the statistical significant value of LB-Q statistics. Open interest as the exogenous variable in conditional variance equation did not reduce the volatility significantly. Hence, it is a prima facie evidence that market information proxy by volume explained the persistence of volatility with asymmetric effect. The empirical results verified that there is a significant relationship between return, volatility, and current volume in the variance equation. Open interest cannot explain the persistence of volatility individually, but it is significant when integrated with volume. The research findings of this paper have important implications for market traders, government, regulatory bodies, and hedgers.